Thematic Learning Based on Local Culture in Implementing National Character Values in Inclusive Referral Elementary School - Setyo Eko Atmojo; Beny Dwi Lukitoaji; Faiz Noormiyanto (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This research aims to develop thematic learning based on local culture as an effort to instill the values of national and state character in inclusive reference primary schools. The novelty of this research lies in the basis of local culture in instilling character values that are implemented in inclusive reference schools. The research method is research and development. The products produced through this research are thematic learning tools based on local wisdom consisting of syllabus, lesson plans, teaching materials, media and evaluation tools. Data collection techniques in this study used observation sheets, questionnaires and test questions. The data analysis technique used   descriptive percentage, difference test (t-test) and improvement test (N-gain). The results of this study indicate the acquisition of a score of more than 4.3 with a maximum score of 5.0 which is in the high validity category. The average frequency of achieving character values in thematic learning based on local culture  is in the high category. Where all aspects of character values appear and are carried out by more than 80% of students in the class. Meanwhile, in the t-test of post-test results, the value of t count = 5.782 > t table = 1.998 and (p) count = 0 <0.05, which means that there is a significant difference in the value of learning achievement between the experimental group using the product developed and the control group. The results of the N gain test showed that the control group had an increase in the medium criteria and the experimental group had an increase in the high criteria so that it was concluded that the thematic learning tools based on local culture had a good level of effectiveness.